Billboard Advertisement Strategies - Shivany, S. (International Journal of Application or Innovation in Engineering & Management, 2018)
Fluctuating buyer requirements and their activities source to be more imaginative in advertising. To be different, to reach the target audiences with effective messages pointed out the need of creative strategic studies. Billboard advertising plays an important role and it should be placed on right place at right moment. Appropriate strategies are needed to have creative advertisements. From the literature this study identified fourteen bill board advertisement approaches for example. Pictorial design concept, Small-Town Warmth, Irreverence, Entertainment and Emotion, The Inherent Drama, Execution, Star Strategy, Positioning, Brand Image, USP (Unique Selling Proposition), Comparative Advertising, Inoculate Advertising, Refutational Advertising, Using Endorsers in Advertising, and Distraction Approaches. Among 35 billboards photographed along the A9 roads of Jaffna, 15 commercial billboards were selected and Discourse analysis was used to analysis to explore strategies of those bill boards. Findings of this study show, that the most of the advertisements have similar strategies such as, emotional appeals, endorsement approach, brand image, Inoculate Advertising, Distraction Approaches, and positioning strategy. In addition, Differentiated, unique featured, or creative and innovative advertisements are scarce in the selected billboard advertisements. This study has the practical implication that, billboard designers and the producer of the billboards should consider new creative ideas in the development of billboards because designing a billboards costs much than the other media. Strategies to the billboard advertisement should have something that will cause a stir enough that people will flick it and share it among the customer groups
Keywords: Billboard advertisements; Creative strategies; Discourse analysis; Jaffna